1991
DOI: 10.1159/000186251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Immunosuppressive Agent, Ciclosporin, on Experimental Immune Complex Glomerulonephritis in Rats

Abstract: Effect of the immunosuppressive agent, ciclosporin (CS), on bovine serum albumin (BSA) nephritis in rats was evaluated. Eight weeks after immunization, 19 male Wistar rats received a daily intravenous dose of BSA (2 mg). Two weeks later, 11 rats received BSA and an oral dose of CS (10 mg/kg), and 8 rats received only BSA for 2 weeks. Urinary protein was measured weekly and serum anti-BSA antibody was measured by passive hemagglutination biweekly. The animals were killed at the 12th experimental week and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In an experimental study, we have reported that CsA suppressed the immune mechanisms responsible for the antibody production seen in immune complex glomerulonephritis in the rat. 13 The early responsiveness of membranous nephropathy to CsA may be related to its hemodynamic effect. 14 It has also been suggested that CsA may improve the barrier dysfunction of GBM that is caused by cell-mediated immunity in membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study, we have reported that CsA suppressed the immune mechanisms responsible for the antibody production seen in immune complex glomerulonephritis in the rat. 13 The early responsiveness of membranous nephropathy to CsA may be related to its hemodynamic effect. 14 It has also been suggested that CsA may improve the barrier dysfunction of GBM that is caused by cell-mediated immunity in membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to explore the efficacy of SPE more comprehensively in a rat model of immune complex glomerulonephritis (ICG) induced by bovine serum albumin (BSA) and complete Freund’s adjuvant (CFA) in an attempt to explain the underlying mechanism, knowing that this animal model is closely relevant to human mesangial proliferative glomerulonephritis (MsPGN) (Fujita et al. 1991 ; Jia and Zou 1996 ).…”
Section: Introductionmentioning
confidence: 99%